Orchestrating T and NK cells for tumor immunotherapy via NKG2A-targeted delivery of a de novo designed IL-2Rβγ agonist - Jie Chen; Enhui Ren; Ze Tao; Hongyu Lu; Yunchuan Huang; Jing Li; Yuzhe Chen; Zhuo Chen; Tianshan She; Hao Yang; Hong Zhu; Xiaofeng Lu (Drug Delivery)
As T and NK cell exhaustion is attributed to increased expression of immune checkpoints and decreased production of proliferative cytokines by these cells, immune checkpoint-targeted delivery of proliferative cytokines might induce robust and sustained antitumor immune responses. Here, the expression profile of NKG2A was first found to be narrower than that of PD-1 in tumor-infiltrated immune cells. Moreover, unlike PD-1, NKG2A was predominantly co-expressed with IL-2Rβγ in tumor-infiltrated CD8+ T and NK cells, but not in Tregs, suggesting that NKG2A might be an ideal target for delivery of IL-2Rβγ agonists to overcome T and NK exhausting. For NKG2A-targeted delivery of an IL-2Rβγ agonist, a single molecule of de novo designed N215 endowed with Immunoglobin G(IgG)-binding ability was coupled to an antibody against NKG2A (αNKG2A) to produce αNKG2A-N215. NKG2A- and IL-2Rβγ-binding were well preserved in αNKG2A-N215, allowing αNKG2A-N215 to act as both an immune checkpoint inhibitor and a T and NK cell stimulator. Intravenously injected αNKG2A-N215 predominantly induced expansion of tumor-infiltrated CD8+ T and NK cells while showing little stimulation of Tregs. Compared with the separate combination using αNKG2A and N215, αNKG2A-N215 exerted a greater antitumor effect in mice bearing MC38 or B16/F1 tumors. 50% of mice bearing MC38 tumors were cured by αNKG2A-N215, and long-term immunological memory against the tumor was induced in these mice. These results indicate that NKG2A is another ideal target for delivery of an IL-2Rβγ agonist, and αNKG2A-N215, with specificities for both NKG2A and IL-2Rβγ, might be developed as a novel agent for immunotherapy.